Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15